Oxidative stress mediates glycidol-induced endothelial injury and its protection by 6-C-(E-2-fluorostyryl)naringenin - Yue Zhou; Hui Xu; Ka-Wing Cheng; Feng Chen; Qian Zhou; Mingfu Wang (Food Science and Human Wellness)
Glycidol is a common lipid-derived foodborne toxicant mainly presents in refined oils and related foodstuffs. Vascular endothelial cells may be potential targets of the deleterious effects associated with glycidol exposure. In human umbilical vein endothelial cells (HUVECs), we found that glycidol treatment promoted endothelialto-mesenchymal transition (EndMT) at a lower concentration (0.5 mmol/L), while induced apoptosis and inflammation at a higher concentration (1 mmol/L). These harmful effects were achieved by the activation of NF-κB/MAPK signaling pathway and were mediated by reactive oxygen species (ROS). In addition, the protective potential of 6-C-(E-2-fluorostyryl)naringenin (6-CEFN) against glycidol was evaluated and compared with naringenin. HUVECs pre-treated with 6-CEFN, but not naringenin, displayed resistance to endothelial dysfunction caused by glycidol.